ANALYSIS KEBUTUHAN PEMBELAJARAN GEOMETRI BERBASIS AUGMENTED REALITY - Lilis Marina Angraini; Sanine Ranisyah; Annisa Mardatillah; Agus Dahlia (Euclid, 2026)
This study presents a comprehensive data analysis of an Augmented Reality (AR)-based geometry learning needs survey of 29 student respondents. The analysis includes user profiles based on gender, evaluation of geometry learning interests and difficulties, preferences for interactive media and educational games, level of AR technology recognition, attitudes toward learning innovations, and student learning motivation. Methods used include data visualization, descriptive statistical analysis, gender comparison, and categorical analysis to identify patterns of student needs and areas for development of learning media. The results provide strategic insights into geometry interests with an average score of 3.13/4.0 (78.2% agreement level), high preference for interactive media (3.08/4.0 or 77.1%), but still low AR recognition (2.30/4.0 or 57.5%). The main findings show a gap between high interest in interactive learning and low recognition of AR technology, indicating an urgent need for socialization programs and development of game-based AR learning media for geometry. The minimal gender gap (maximum 0.28 points) allows for the implementation of universal strategies without the need for significant gender-based customization.